Body Language Detecting Deception: Fatima Fatima - Fatima, Fatima Fatima (International Journal for Electronic Crime Investigation, 2020)
Abstract The objective of this review paper is to discuss the understanding of body language deception. This study explains a detail interpretation of body language also known as nonverbal cues including facial expressions called micro-expressions and other bodily moves of speakers/suspects during interviews and investigation process. It will emphasize on importance of reading body language in criminal investigation for lie detection and proper training of investigators/interviewers for an effective interrogation. It explains proper documentation of nonverbal cues and recording them for further assistance in multiple interviews in future as these cues remain for a short time. It will enlighten the effects of gender, social and economic status on body language and their resulting cues. A proper knowledge and training of reading nonverbal behaviors can increase forensic application of body language in criminal justice system for the identification of the right guilty party.